1999
DOI: 10.1039/a905245c
|View full text |Cite
|
Sign up to set email alerts
|

New supramolecular packing motifs: π-stacked rods encased in triply-helical hydrogen bonded amide strands

Abstract: The structure of N,NA,NB-tris(2-methoxyethyl)benzene-1,3,5-tricarboxamide consists of aryl rings self-assembled using a novel conjunction of organizational motifs into a pstack surrounded by a triple helical network of hydrogen bonds, in a manner suggestive of a new mode of organization for some columnar liquid crystals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
169
1
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(180 citation statements)
references
References 17 publications
8
169
1
2
Order By: Relevance
“…This generates an ideal self-complementary building block to be held by N-H-O and N-H-N hydrogen bonds. This supramolecular structure differs from that of Lightfoot et al [10] and of Palmans et al [12] The unit cell contains two amide and four methanol solvent molecules. Pairs of amide molecules related by an inversion centre are connected into dimers via two N-H/O carbonyl and two N-H/N pyridyl intermolecular hydrogen bonds.…”
Section: Resultscontrasting
confidence: 44%
See 2 more Smart Citations
“…This generates an ideal self-complementary building block to be held by N-H-O and N-H-N hydrogen bonds. This supramolecular structure differs from that of Lightfoot et al [10] and of Palmans et al [12] The unit cell contains two amide and four methanol solvent molecules. Pairs of amide molecules related by an inversion centre are connected into dimers via two N-H/O carbonyl and two N-H/N pyridyl intermolecular hydrogen bonds.…”
Section: Resultscontrasting
confidence: 44%
“…Only three reports of structures are known in which an aromatic ring has been used as the scaffold for three peptide strands [10][11][12]. In these and other related structures the aromatic rings typically adopt one of several known conformations, of which the most common are edge-face, offset stacked and face-face stacked [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This motif forms 1-D columnar structures in solution as well as in the solid state as a result of a threefold intermolecular hydrogen bonding in a helical type of arrangement. [138][139][140] However, the amount of publications where they are applied as solid supramolecular materials is limited. Mes et al reported on the use of BTA motif for a supramolecular material based on phasesegregated nanorods in a polymer poly(ethylene butylene) (PEB) matrix.…”
Section: Supramolecular Polymers Based On Benzene-135-tricarboxamidmentioning
confidence: 99%
“…The corrole rings in 1 are coupled to a central trimesic amide core, a motif which is well known for its ability to form extended hydrogenbonded 1D columnar stacks. [20][21][22] Although corroles are slightly less planar than porphyrins, 23,24 it can be expected that, just like in the case of the related porphyrin trimers, 10 the columnar stacks formed by 1 are further stabilised by p-p stacking interactions between the corrole side groups (Fig. 1).…”
mentioning
confidence: 99%